NLR Is Associated With Geriatric Depression in Chinese Women: A Community-Based Cross-Sectional Study in Eastern China - Liang, Meng; Du, Bingying; Zhang, Hailing; Lu, Xiaoyan; Chen, Chao; Fan, Cunxiu; Bi, Xiaoying (Frontiers in Psychology, 2020)
IIn recent years, the prevalence of depression has been increasing, causing a serious global burden of disease. Previous studies have proved that low-grade inflammation is involved in the process of depression. To explore the role of inflammation in the pathogenesis of senile depression, neutrophil to lymphocyte ratio(NLR) was used in this study, as a biological marker for non-specific inflammation. The present study was conducted among elderly adults from a randomly selected Community in Yangpu District, Shanghai from November 1st to December 30th, 2017. 665 participants were included in the present study, including 276 males(median age was 68 years old) and 389 females(median age was 67 years old). NLR was calculated based on results of hematology examination. Depressive symptoms were assessed using the simplified version of Geriatric Depression Scale(GDS), the participant with total score greater than 5 points was considered to be depressed. The association between NLR and depression was evaluated separately for men and women. The prevalence of depression was 35.1% for men and 34.4% for women. No associations were found between NLR and depression among males. Nevertheless, compared with normal women, NLR was significantly increased in women with depressive symptoms(P=0.020). Logistic regression analysis showed that NLR was independently associated with geriatric depression in women. The odds ratios(ORs) of depression was 2.152(1.095, 4.227; p=0.026) for the fourth compared with the first quartile of NLR. In conclusion, this study showed increased NLR was significantly associated with geriatric depression in women, but not men.